Effect of non-surgical periodontal treatment on clinical signs of rheumatoid arthritis - Fazele Atarbashi-Moghadam; Fahimeh Rashidi Maybodi; Ali Dehghan; Alireza Haerian Ardakani (Tabriz University of Medical Sciences, 2018)
Background. Several studies have shown the association between periodontitis and rheumatoid arthritis (RA) and some similarities in the pathogenesis of these two diseases but clinical trials which have evaluated the effect of periodontal therapy on clinical signs of active RA are scarce, particularly in Iran. The aim of this study was to evaluate the effect of non-surgical periodontal treatment on the improvement of clinical signs of patients with RA. Methods. Fifty-six patients with active RA and generalized moderate-to-severe chronic periodontitis were selected and divided into case (periodontal treatment) and control (without periodontal treatment) groups. Periodontal parameters and RA disease activity scores (DAS28 index) were compared at 6- and 12-week intervals. Results. In the case group, a significant reduction in all the periodontal indices was observed 6 weeks after treatment. At the 12-week evaluation, periodontal indices showed a significant reduction in comparison with baseline and a little increase in comparison with 6-week interval. Six weeks after treatment, DAS28 decreased significantly in the case group (P<0.05). DAS28 also decreased at 12-week interval but its reduction was not significant in comparison with 6-week interval. DAS28 in the case group at 12-week interval was significantly less than that in the control group (P<0.05). Conclusion. Since periodontal care as a part of treatment protocol in RA patients can be effective in improving clinical signs, the recall intervals are better to be 3 months or shorter.